Corporate Governance and Financial Regulatory Framework in Nigeria: Issues and Challenges - Abdulmalik, S. O.; Ahmad, A. C. (Journal of Advanced Research in Business and Management Studies, 2020)
The aim of this paper is to identify those factors that are peculiar to Nigeria which are likely to challenge the beneficial impact of the new accounting and corporate governance regulatory initiative in the country by using available anecdotal and empirical evidence. Based on our review, we find out that poor monitoring and compliance mechanisms arising from conflicting regulatory laws and the impairment of board of directors and auditor independence arising from the nature of firm ownership structure in Nigeria contribute to the failure in accounting and corporate governance practise. Of which if not address the ongoing effort by the Nigeria government to strengthen financial reporting atmosphere in Nigeria might not be realizable. Therefore, this study recommends that future accounting and corporate governance regulatory reforms in Nigeria should take into account the country institutional setting.